Human skin penetration of hyaluronic acid of different molecular weights as probed by Raman spectroscopy. Issue 1 (16th April 2015) - Essendoubi, M.; Gobinet, C.; Reynaud, R.; Angiboust, J. F.; Manfait, M.; Piot, O.
Abstract : Background: Topical delivery of molecules into the human skin is one of the main issues in dermatology and cosmetology. Several techniques were developed to study molecules penetration into the human skin. Although widely accepted, the conventional methods such as Franz diffusion cells are unable to provide the accurate localization of actives in the skin layers. A different approach based on Raman spectroscopy has been proposed to follow‐up the permeation of actives. It presents a high molecular specificity to distinguish exogenous molecules from skin constituents. Methods: Raman micro‐imaging was applied to monitor the skin penetration of hyaluronic acids (HA) of different molecular weights. The first step, was the spectral characterization of these HA. After, we have determined spectral features of HA by which they can be detected in the skin. In the second part, transverse skin sections were realized and spectral images were recorded. Results: Our results show a difference of skin permeation of the three HA. Indeed, HA with low molecular weight (20–300 kDa) passes through the stratum corneum in contrast of the impermeability of high molecular weight HA (1000–1400 kDa). Conclusion: Raman spectroscopy represents an analytical, non‐destructive, and dynamic method to evaluate the permeation of actives in the skin layers.